Optimization of Urban Public Transportation System in Vijayawada - A Case Study - Prakash Koganti, Shyam; Hemantha Raja, Kommineni; Satish, Sajja; Sai Narendra, M (International Journal of Engineering and Technology, 2018)
The recent scenario of Public transportation in most of the Indian cities shows only 20% to 30% of the total passengers utilizing any public transit as their mode of travel. Rapid growth in vehicles population has put enormous strains in all urban roads in Vijayawada, due to high vehicle ownership and poor supporting public transport facilities specially in the cities where the population is between 1 to 2 million. With more private vehicles on roads, pollution as well as congestion levels in the cities are also expected to increase. The major factor is very low ridership in public transport due to poor service quality and more travelling time. Hence there is a need to make the public transit a favorable mode of transport for the passengers. This study is concerned of assessment of public transport demand for Vijayawada and identifies the major factors for poor ridership with estimation of the probable shift of personal vehicle users to bus due to the increase in its level of service also identifies ways to account qualitative factors in the public transport project evaluation by adjusting travel time values to reflect comfort and convenience.Â Â